ANALISIS HARGA KAYU LAPIS TERHADAP NEGARA PESAING : Kasus Malaysia (A Price Analysis of Plywood on Competitor Country : Case of Malaysia - Rachman Effendi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
Nowadays, the role of timber industry in Malaysia becomes more important. The rapid growth of timber industry can be illustrated by the increase of the production level of plywood and veneer. An annual increase of plywood production since 1960 to 1988 was 1,519 % The increase of plywood production is facing a number of problems such as decreasing in supply of logs, furher processing of log is still undeveloped, competition from non wood materials such as steel, concrete, alumunium and plastic,. Also price competition with competitor countries such as Indonesia and Philippine. The objectives of this paper is to study the timber industry development, especially plywood industry and economic factors which influenced Malaysia's plywood price where. a multiple regression analysis was used to analyze the plywood price.The results of the analysis shows that export price of plywood from the competitor countries especially indonesia and Philippines has influenced very significantly to the price fluctuation of Malaysia plywood. It explained up to 88 % of the price fluctuations. the remaining 12 % is explained by some other factors. In other words, the competitions price is the most prominant factor in determining the price fluctuation of Malaysian plywood.